Nonlinear Control Methods for Single-Ended Primary-Inductor Power Converters - Biricik, Samet; Tuan Ngo; Komurcugil, Hasan; Basu, Malabika (IEEE, 2017)
This paper investigates nonlinear control methods for single-ended primary-inductor converters (SEPIC). The fast switching and average models show the converter nonlinearity in terms of inductor currents, capacitor voltages, and the switching duty cycle. The control law intuitively should be nonlinear to drive and guarantee the system stability. Two different control laws based on the passivity and back-stepping technique are examined and designed to have asymptotically global stability in the system. Unlike the passivity method which regulates the duty cycle directly, the back-stepping method adjusts the switching duty by a driver integrator/low pass filter system. The simulation results have shown the benefits from the passivity control law over the back-stepping one. Moreover, an observer is introduced in order to reduce the number of voltage and current sensors for the control system. The nonlinear control law is thus a combination of the measured signal and the estimated ones. Simulation results are also presented to verify the effectiveness of the observer in the control system.
43rd Annual Conference of the IEEE-Industrial-Electronics-Society (IECON) -- OCT 29-NOV 01, 2017 -- Beijing, PEOPLES R CHINA
Keywords: DC-DC power converters; Nonlinear control systems; Observers; Feedback; State estimation